Business Cycles in South America and East Asia: An Introduction - Cunha, Alexandre Barros da (2005)
We study the business cycle component of the per capita gross domestic product of ten South American and six East Asian countries during the period 1970-2000. Both sets of countries display an average volatility roughly equal to twice the U.S. one. Average persistence in each of these areas is similar to the U.S. The cyclical phases usually do not coincide temporally across countries.